Socioemotional Skills in Early Childhood: Evidence from a Maternal Psychosocial Intervention - Dilek Sevim; Victoria Baranov; Sonia R. Bhalotra; Joanna Maselko; Pietro Biroli (Institute of Labor Economics (IZA), 2023)
We study the formation of social and emotional skills in the first three years of life, and investigate the impact of a cluster-randomized peer-led psychosocial intervention targeting perinatally depressed mothers in rural Pakistan. The intervention significantly improved maternal mental health, especially among mothers of boys. It resulted in imprecisely estimated increases in parental investment, and modest but transitory improvements in child's socioemotional skills. A descriptive analysis of mechanisms reveals that the intervention modified the production function of children's skills, by lowering the productivity of maternal mental health in the first 12 months of life. It moved outcomes for depressed women closer to outcomes for women not depressed during pregnancy.
Keywords: D1; I1; J1; O2; 330; child development; RCT; socioemotional; stress; mental health; technology of skill formation; gender